MODIFIABLE NON-GENETIC FACTORS ASSOCIATED WITH ADHERENCE TO ANTIHYPERTENSIVE DRUG THERAPY - Maria Zoraida Rojas-Marín, Diana Marcela Buitrago, Yadira Moyano; Alexander Casallas Vega (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Background: Adherence to pharmacological treatment is considered a public health problem, so it is necessary to identify the factors and variables of each patient, to develop strategies that improve adherence. Aims: to examine the relationship between adherence profiles and sociodemographic factors and their association with medication adherence in patients with hypertension. Methods: Methods: Cross-sectional study in hypertensive patients from the HTA program at the Chía clinic, Colombia. Adherence to medications was assessed using the Morisky-Green (MMAS-4) instrument and the Bonilla (BT) test, and some variables from the clinical history. A descriptive and bivariate analysis was performed to determine the assessment between variables and adherence. The nonparametric Mann-Whitney U test was used for continuous variables, while the chi-square test was used for categorical variables. All tests were performed with an alpha level of 0.05 and a p <0.01. Results: Results: The sample consisted of 116 patients, the majority being over 60 years of age (71%), with a predominance of females (70%), with a high level of involvement in domestic responsibilities (50%), living in urban areas (61%), belonging to a low socioeconomic stratum (72%), with income below the Colombian minimum wage (equivalent to 323 dollars, 64%), with complete secondary education (58.77%). The majority are married (43%). Regarding TMG, the prevalence of non-adherence to treatment was 58.62%. In the case of TB, the prevalence of risk of non-adherence was 65.62%. No significant association was found between the variables evaluated and lack of adherence. Conclusion: The results indicate no notable correlation between the sociodemographic variables and the lack of adherence to treatment in hypertensive patients. However, a considerable proportion of hypertensive patients need to adhere to their treatment regimens. Consequently, further research is necessary to elucidate the underlying factors contributing to this non-adherence and to develop effective strategies to address these challenges.